Structural model of lymphocyte receptor NKR-P1C revealed by mass spectrometry and molecular modeling - Rozbesky, Daniel; Sovova, Zofie; Marcoux, Julien; Man, Petr; Ettrich, Rudiger; Robinson, Carol V; Novak, Petr (Analytical chemistry, 2013)
NKR-P1C is an activating immune receptor expressed on the surface of mouse natural killer cells. It has been widely used as a marker for NK cell identification in different mice strains. Recently we solved a crystal structure of the C-type lectin-like domain of a homologous protein, NKR-P1A, using X-ray crystallography and also described the strategy for rapid characterization of the protein conformation in solution. This procedure utilized chemical cross-linking, hydrogen/deuterium exchange, and molecular modeling. It was found that the solution structure differs from the crystal structure in the conformation of the loop region. The loop, detached from the protein compact core in the crystal structure, is closely attached to the core of the protein in solution. Here we present and interpret the solution structure of the C-type lectin-like domain of NKR-P1C using chemical cross-linking and molecular modeling. The validation of the model and conformation of the loop region in NKR-P1C were addressed using ion-mobility mass spectrometry.
Keywords: Antigens, Ly; Models, Molecular; Humans; Mass Spectrometry; antigeny Ly; Lymphocytes; lymfocyty; Protein Structure, Secondary; Molecular Sequence Data; molekulární sekvence - údaje; krystalografie rentgenová; Crystallography, X-Ray; lidé; sekundární struktura proteinů; zvířata; myši; molekulární modely; myši inbrední C57BL; Mice; NK Cell Lectin-Like Receptor Subfamily B; Amino Acid Sequence; Mice, Inbred C57BL; lektinové receptory NK-buněk - podrodina B; Animals; hmotnostní spektrometrie; sekvence aminokyselin